Klauzura północno-wschodniej Azji na mapach średniowiecznych i wczesnonowożytnych - Kochanek, Piotr (Vox Patrum, 2016)
The present article explores 44 medieval and early modern world maps. The subject of research are three graphic topoi, that evoke the image of the biblical and historical enemy from the north: Gog and Magog, Caspian Gates (Portae Caspiae) and the inclosed nations (inclusae nationes). These topoi were localized in north-east Asia. For this reason the title of the article includes the concept of the enclosed area of north-east Asia. There are also analyzed vignettes of the cities, which are located on the territory of the enclosed area. The aim of the article is to show the changes which over several centuries have occurred within the interpretation of these three topoi. This evolution has been closely associated with the expansion of geographical horizon of Europeans. Geopolitical and historical changes were also an important factor of this evolution. All these elements have an impact on the way of looking at the enclosed area of north-east Asia. Important factor was also philosophy and theology. Slows fear of the enemy from the north gave way to curiosity, and curiosity prompted the Europeans to get to know this part of Asia. Graphical topos has been replaced by geographical knowledge, that has been transferred to the maps.